Effect of Environmental Conditions on the Formation of the Viable but Nonculturable State of Pediococcus acidilactici BM-PA17927 and Its Control and Detection in Food System - Li, Yanmei; Huang, Teng-Yi; Mao, Yuzhu; Chen, Yanni; Shi, Fan; Peng, Ruixin; Chen, Jinxuan; Bai, Caiying; Chen, Ling; Wang, Kan; Liu, Junyan (Frontiers in Microbiology, 2020)
Objective: This study aimed to investigate the effect of environmental conditions including nutrient content, acetic acid concentration, salt concentration, and temperature on the formation of viable but nonculturable (VBNC) state of P. acidilactici, as well as its control and detection in food system. Methods: Representing various environmental conditions in different food systems, 16 induction groups were designed for the formation of VBNC state of P. acidilactici. Traditional plate counting was applied to measure the culturable cell numbers and Live/Dead Bacterial Viability Kit combined with Fluorescent microscopy was used to identify viable cells numbers. The inhibition of bacterial growth and VBNC state formation by adjusting the environmental conditions were investigated, and the clearance effect of VBNC cells in crystal cake system was studied. In addition, a propidium monoazide-polymerase chain reaction (PMA-PCR) assay was applied to detect the VBNC P. acidilactici cells in crystal cake food system. Results: Among the environmental conditions included in this study, acetic acid concentration had the greatest effect on the formation of VBNC state of P. acidilactici, followed by nutritional conditions and salt concentration. Reducing nutrients in the environment and treating with 1.0% acetic acid can inhibit P. acidilactici from entering the VBNC state. In the crystal cake system, the growth of P. acidilactici and the formation of VBNC state can be inhibited by adding 1.0% acetic acid and storing at -20°C. In crystal cake system, the PMA-PCR assay can be used to detect VBNC P. acidilactici cells at a concentration higher than 104 cells/mL. Conclusions: The VBNC state of P. acidilactici can be influenced by the changing of environmental conditions, and PMA-PCR assay can be applied in food system for the detection of VBNC P. acidilactici cells.